The Arce Tephra: two subsequent paroxysmal Plinian eruptions from Coatepeque Caldera (El Salvador) - Kutterolf, Steffen; Schindlbeck, Julie Christin; Rohr, I.; Rademacher, M.; Cisneros de León, Alejandro; Eisele, S.; Freundt, A.; Hernandez, W.; Wang, K. -L. (Journal of volcanology and geothermal research, 2020)
The Coatepeque volcanic complex in El Salvador produced at least four Plinian eruptions within the last 80 kyr. The eruption of the 72 ka old Arce Tephra formed the Coatepeque Caldera and was one of the most powerful explosive eruptions in El Salvador. Hitherto it was thought that the Arce tephra had been emplaced only by one, mostly Plinian, eruptive event that ended with the deposition of a thick ignimbrite. However, our stratigraphic, geochemical, and zircon data reveal a temporally closely- spaced double eruption separated by a gap of only a couple of hundred years, and we therefore distinguish Lower and Upper Arce Tephras. Both eruptions produced in the beginning a series of fallout units generated from fluctuating eruption columns and turning wind directions. The final phase of the Upper Arce eruption produced surge deposits by several eruption column collapses before the terminal phase of catastrophic ignimbrite eruption and caldera collapse. Mapping of the individual tephra units including the occurrences of distal marine and lacustrine ash layers in the Pacific Ocean, the Guatemalan lowlands and the Caribbean Sea, result in 25.6km3 tephra volume, areal distribution of 4×105km2 and eruption column heights between 20-33km for the Lower Arce eruption, and 40.5km3 tephra volume, including 10km3 for the ignimbrite, distributed across 6×105km2 and eruption column heights of 23-28km for the Upper Arce eruption. These values and the detailed eruptive sequence emphasize the great hazard potential of possible future highly explosive eruptions at Coatepeque Caldera, especially for this kind of double eruption.